Causal relationship between the immune cells and ankylosing spondylitis: univariable, bidirectional, and multivariable Mendelian randomization - Qin, Chaofan; Yu, Qingshuai; Deng, Zhongliang; Zhang, You; Chen, Mingxin; Wang, Xin; Hu, Tao; Lei, Bo; Yan, Zhengjian; Cheng, Si (Frontiers in Immunology, 2024)
Background: Ankylosing spondylitis (AS) is an autoimmune disease that affects millions of individuals. Immune cells have been recognized as a crucial role in the pathogenesis of AS. However, the relationship has not been fully explored.We chose to employ mendelian randomization (MR) to investigate the potential correlation between immune cells and AS. The data for immune cells are sourced from the latest genome-wide association studies (GWAS). Data for AS were obtained from the FinnGen consortium. Our comprehensive univariable MR analysis covered 731 immune cells to explore the potential causal relationship with AS. The primary analysis method was inverse variance weighting (IVW). Additionally, Cochran's Q test and MR-Egger intercept test were used to assess the presence of pleiotropy and heterogeneity. We examined whether our results could be influenced by individual SNPs using the leave-one-out test. We conducted a bidirectional MR to investigate the reverse relationship. We also applied multivariable MR to decrease the potential influence between the immune cells.Result: Overall, our univariable MR analysis revealed 8 immune cells associated with AS. Among these, 4 immune cells contributed to an increased risk of AS, while 4 immune cells were identified as protective factors for AS. However, the Bonferroni test confirmed only 1 risk factor and 1 protective factor with a significance level of p<6.84E-05. CD8 on Effector Memory CD8 + T cell could increase the risk of AS (P:1.2302E-05, OR:2.9871, 95%CI:1.8289-4.8786). HLA DR on CD33 dim HLA DR + CD11b + could decrease the risk of AS (P:1.2301E-06, OR:0.5446, 95%CI: 0.4260-06962). We also identified a bidirectional relationship between CD4 on CD39 + activated CD4 regulatory T cells and AS by utilizing the bidirectional MR. To address potential confounding among immune cells, we employed multivariable MR analysis, which revealed that only one immune cell had an independent effect on AS. HLA DR on CD33 dim HLA DR + CD11b + could decrease the risk of AS (P:2.113E-06, OR:0.0.5423, 95%CI:0.4210-0.6983). Our findings were consistently stable and reliable.Our findings indicated a potential link between immune cells and AS, which could provide a new idea for future research. Nevertheless, the specific underlying mechanisms require further exploration.